Dampak Learning Loss terhadap Psikososial Mahasiswa Saat dan Pasca Pandemi Covid-19 - Alfi Sihati; Iefone Shiflana Habiba; Salsabila Difany; Hanif Cahyo Adi Kistoro (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2022)
The COVID-19 pandemic has had a wide impact on all walks of life. One of the effects that is very pronounced is the social aspect. The purpose of this study was to determine the impact of learning loss on psychosocial students during and after the pandemic. The research method used is a qualitative research method with a phenomenological approach. The participants in this study were students from three Islamic universities in Yogyakarta, totaling 15 people. The selection of participants was based on criteria that had been determined purposively, namely from Islamic colleges, experienced social problems in particular and data could be taken. The data collection technique used in-depth interviews in accordance with the interview instrument guidelines that had been made. The data analysis technique went through three stages, namely reduction, data presentation and data interpretation to draw conclusions. The research findings lead to three conclusions. First, the impact of the pandemic is the loss of enthusiasm for learning or learning loss. Second, socially, the impact of the pandemic causes psychosocial problems, namely they tend to be aloof or introverted. Third, after the pandemic, most of the students are already comfortable with their conditions during the pandemic, so they experience laziness and boredom to carry out activities directly. The results of this study still have many weaknesses, especially in the selection of respondents who are still limited and data mining and analysis. Subsequent research will be urgently needed to provide more comprehensive reinforcement and additional results.